Energy assessment and reporting method. (Chartered Institution of Building Services Engineers, 2006)
This document describes a method for assessing the energy performance of an occupied building based on metered energy use, and includes a software implementation of the method. Recent UK and European initiatives mean that the benefits of performance assessment are being backed by legislation. TM22 and its software provides support for these assessment needs. While primarily directed at assessing energy performance, the procedure has a wide range of uses for building managers, design professionals, and energy management specialists contributing to the 'virtuous circle' of good building management and satisfied occupants. -- Provided by publisher.
Publisher's no.: CIBSE TM22: 2006.
Keywords: Buildings -- Energy consumption.; Buildings -- Energy conservation.; Buildings -- Environmental engineering.; elektronické knihy; electronic books